1994
DOI: 10.1177/016264349401200303
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Visualization—A Gateway to Computer-Based Technology

Abstract: The positive impact of computer-based technology in education varies in part as a function of the individual abilities of users. A model is proposed for how individual differences are expected to affect performance when technology is introduced. The primary cognitive factor driving differences in performance using computer-based technology is spatial visualization ability. Four techniques for mitigating the negative impact of low spatial visualization are discussed. The use of spatial metaphors and graphical u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 17 publications
1
44
0
4
Order By: Relevance
“…As computer skills have become increasingly important in engineering education, it interesting that Norman found that an individual's spatial skill level is the most significant predictor of success in his/her ability to interact with and take advantage of the computer interfaces [9].…”
Section: Why Are Spatial Visualization Skills Important?mentioning
confidence: 99%
“…As computer skills have become increasingly important in engineering education, it interesting that Norman found that an individual's spatial skill level is the most significant predictor of success in his/her ability to interact with and take advantage of the computer interfaces [9].…”
Section: Why Are Spatial Visualization Skills Important?mentioning
confidence: 99%
“…A considerable number of studies underline the importance of spatial orientation processes for the proper handling of technical devices [4,5,9,10,11,12,13], especially small screen devices [1,2,6]. When interacting with complex menu structures, users need to build up a mental representation of the spatial structure of that menu in order to orient themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The intent is to expand this study in the future to areas of object dimensioning and tolerancing. In addition to research conducted by Norman (1994), where he found that a person's spatial skill level was the most significant predictor of success in their ability to interact with and take advantage of the computer interface 6 , Sorby (1999) concluded in response to a study conducted at MTU that in order to develop 3-D spatial skills, the answer is sketching, sketching, sketching 7 . Parallel to analytical introductions of projection methods, students are asked to complete in-class sketching exercises of progressing complexity.…”
Section: Methodsmentioning
confidence: 99%